Single ring isolation of pulmonary veins combined with electrical isolation of the superior vena cava in patients with paroxysmal atrial fibrillation - Li, Xi; Chen, Yanhong; Chen, Guanghui; Deng, Chengang; Tang, Chen; Zhang, Jinlin (Frontiers in Cardiovascular Medicine, 2023)
Background Single-ring isolation (SRI) of the pulmonary veins and the left atrial post wall (LAPW) is an accepted strategy in atrial fibrillation ablation. Whether SRI combined with superior vena cava isolation (SVCI) could further increase the success rate of paroxysmal atrial fibrillation (PAF) has not been reported. Objective This study aimed to investigate whether SRI combined with SVCI was feasible and whether it could improve the success rate of PAF ablation. Methods and results In our study, sixty patients with PAF from May 2019 to March 2021 were included. SRI plus SVCI was completed with ablation index (AI)-guided high-power ablation. The success rates of SRI and SVCI were 100% and 97%, respectively. One-pass SRI was achieved in 41 out of 60 patients, with 19 out of 60 patients requiring additional ablation to complete the SRI. SVC was not isolated in 2 out of the 60 cases due to concerns about the phrenic nerve (PN) injury. Among the enrolled patients, 2 patients had anomalous pulmonary veins (PVs) (common ostium of inferior PVs). SRI was applied to achieve the PV and PW isolation. After ablation, one patient had an ischemic stroke but recovered without severe morbidity. The average follow-up period was (20 ± 7) months, and single-procedure freedom from atrial arrhythmia was 91.7%. AT/AF recurred in five patients, and 2 out of 5 patients underwent redo ablation. The multi-procedure freedom from atrial arrhythmia was 95%. Conclusion Our novel ablation strategy, SRI combined with SVCI, in patients with PAF was feasible and safe, with a relatively high success rate.